Profiles and predictors of thriving in children on the autism spectrum. (31st January 2022) - Simpson, Kate; Clark, Megan; Adams, Dawn
Abstract: Background: Thriving is defined as the growth of attributes that mark a flourishing, healthy individual and include Competence, Confidence, Connectedness, Character, Caring and Contribution to self, family, community and civil society. Thriving has been linked to positive youth outcomes in neurotypical children and adolescents but has rarely been explored for individuals on the autism spectrum. Method: This study explored the profiles and predictors of parent‐reported thriving in 111 school children on the autism spectrum, aged 6 to 14 years. Results: Parents rated children as having relative strengths in the Caring and Connectedness dimensions and relative challenges in the Competence dimension. Stronger thriving outcomes were consistently predicted by stronger socialization scores; however, the other predictors of outcome differed by dimensions. Conclusion: The current findings provide insight into the individual and contextual factors that predict thriving in children on the autism spectrum. As research into thriving is in its infancy, more work is needed to understand how child, family and contextual factors relate to thriving in individuals on the autism spectrum to foster positive outcomes.